(untitled) - Kawakami, Kenji (London, 1995)
Some say that laughter has curative properties. I highly recommend this book as a gift for sick people. I enjoyed it so much myself that I gave a copy to a friend in the hospital for major surgery, warning her not to read it until her stitches could bear the strain of laughing, and it was a tremendous hit. I am ordering more now for other ill friends. None of the inventions are commercially viable; the book says that if any should come on the market, they will be removed from the "chindogu" list. Nevertheless, there is a certain silly logic to them that makes most of them hilarious.
Keywords: Social,Xã hội; Japan,Nhật Bản